Handbook of adhesive bonded structural repair - Wegman, Raymond F. (Noyes Publications, 1992)
This Handbook provides methods of repair for adhesive bonded and composite structures, the identification of suitable materials and equipment for repairs, and methods of inspection before and after repair. Repair methods included are for composite laminates containing fiberglass, graphite, or Kevlar reinforcements in organic matrices, and sandwich structures containing honeycomb, foam or balsa cores with either metallic or composite laminate skins. Materials, tools, and equipment used in repairs are also described and their sources are presented.
Keywords: Sandwich construction.; Adhesive joints -- Repairing.; Composite materials.; Laminated materials.; elektronické knihy; electronic books